Feces Derived Allergens of Tyrophagus putrescentiae Reared on Dried Dog Food and Evidence of the Strong Nutritional Interaction between the Mite and Bacillus cereus Producing Protease Bacillolysins and Exo-chitinases - Erban, Tomas; Rybanska, Dagmar; Harant, Karel; Hortova, Bronislava; Hubert, Jan (Frontiers in Physiology, 2016)
Tyrophagus putrescentiae (Schrank, 1781) is an emerging source of allergens in stored products and homes. Feces proteases are the major allergens of astigmatid mites (Acari: Acaridida). In addition, the mites are carriers of microorganisms and microbial adjuvant compounds that stimulate innate signaling pathways. We sought to analyze the mite feces proteome, proteolytic activities and mite-bacterial interaction in dry dog food. Proteomic methods comprising enzymatic and zymographic analysis of proteases and 2D-E-MS/MS were performed. The highest protease activity was assigned to trypsin-like proteases; lower activity was assigned to chymotrypsin-like proteases, and the cysteine protease cathepsin B-like had very low activity. The 2D-E-MS/MS proteomic analysis identified mite trypsin allergen Tyr p3, fatty acid-binding protein Tyr p13 and putative mite allergens ferritin (Grp 30) and (poly)ubiquitins. Tyr p3 was detected at different positions of the 2D-E. It indicates presence of zymogen at basic pI, and mature-enzyme form and enzyme fragment at acidic pI. Bacillolysins (neutral and alkaline proteases) of Bacillus cereus symbiont can contribute to the protease activity of the mite extract. The bacterial exo-chitinases likely contribute to degradation of mite exuviae, mite bodies or food boluses consisting of chitin, including the peritrophic membrane. Thus, the chitinases disrupt the feces and facilitate release of the allergens. B. cereus was isolated and identified based on amplification and sequencing of 16S rRNA and motB genes. B. cereus was added into high-fat, high-protein (dry dog food) and low-fat, low-protein (flour) diets to 1% and 5% (w/w), and the diets palatability was evaluated in 21-day population growth test. The supplementation of diet with B. cereus significantly suppressed population growth and the suppressive effect was higher in the high-fat, high-protein diet than in the low-fat, low-protein food. Thus, B. cereus has to coexist with the mite in balance to be beneficial for the mite. The mite-B. cereus symbiosis can be beneficial-suppressive at some level. The results increase the veterinary and medical importance of the allergens detected in feces. The B. cereus enzymes/toxins are important components of mite allergens. The strong symbiotic association of T. putrescentiae with B. cereus in dry dog food was indicated.